2022
DOI: 10.1371/journal.pone.0274449
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health service utilization among mothers for under-five children: A cross-sectional study in Khulna district of Bangladesh

Abstract: Although Bangladesh has made significant progress in reducing child mortality, proper utilization of health services for under-five children among mothers remains one of the major challenges. Hence, this study was designed to investigate the factors influencing health service utilization among mothers for under-five children in the Khulna district of Bangladesh. Administering a semi-structured interview schedule, data were collected from 364 randomly selected mothers from the study area between June and August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These conditions can impact the ability of residents to adopt and implement recommended ENC practices due to resource constraints and a lack of awareness [31]. Thirdly, cultural and educational differences among urban populations can in uence healthcareseeking behaviors and adherence to ENC guidelines [32]. Factors such as education levels, awareness campaigns, and community norms play a signi cant role in shaping maternal and newborn care practices [6].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions can impact the ability of residents to adopt and implement recommended ENC practices due to resource constraints and a lack of awareness [31]. Thirdly, cultural and educational differences among urban populations can in uence healthcareseeking behaviors and adherence to ENC guidelines [32]. Factors such as education levels, awareness campaigns, and community norms play a signi cant role in shaping maternal and newborn care practices [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in Bangladesh by Akter et al . [ 17 ] revealed a lack of knowledge about preventive measures and health promotion activities, resulting in limited healthcare utilization. These studies support the notion that inadequate awareness and knowledge about available healthcare services can act as significant barriers to utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Prinja et al ,[ 16 ] Jahan et al ,[ 5 ] and Akter et al . [ 17 ] all identified financial constraints as a major barrier to healthcare utilization. These studies demonstrated that the inability to afford medical expenses, transportation costs, and medications often leads to delayed or forgone healthcare seeking.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental objective of the current study was to understand the antepartum care utilization pattern among the Garo indigenous women. Although a previous study found that antepartum care-seeking is less proportionate among rural Garo moms compared to urban Garo women, other indigenous women, and non-indigenous women [ 55 ], similar to a substantial number of other studies focused on maternal health care-seeking behavior [ 39 , 40 , 56 , 57 ], it considered the indigenous women as a homogenous group. The author argues that it is insufficient to investigate the pattern of antepartum biomedical care uptake among women by considering them as a homogenous group and, thus, approached the Garo indigenous mothers as a heterogeneous group to understand one particular issue by listening to their less-heard voices.…”
Section: Introductionmentioning
confidence: 99%
“…The behavioral model, developed in 1968 by Ronald M. Andersen, a US medical sociologist and expert on healthcare [ 8 ], is the most frequently suggested framework for understanding healthcare service uptake [ 58 ]. It has been used to guide the examination of predictors associated with the utilization of healthcare services [ 56 ] According to this model, the uptake of healthcare services depends on three fundamental issues [ 8 ]. These are: (1) predisposing characteristics (e.g., age, family size, educational level, birth order, and health belief), (2) enabling characteristics, including income, availability of health care centers and services, the quality of the care services, and (3) need characteristics (i.e., nature of the illness, perceived understanding of health status, the perceived need for health care, and expected satisfaction from the received services).…”
Section: Introductionmentioning
confidence: 99%